Confessional disputes in the republic of letters: Susan Du Verger and Margaret Cavendish. Issue 2 (15th March 2019) - Begley, Justin
ABSTRACT: The starting point of this article is an understudied piece of critical exegesis from 1657 titled Humble Reflections Upon Some Passages of the Right Honorable the Lady Marchionesse of Newcastles Olio . An obscure Englishwoman named Susan Du Verger composed this 164-page tract to refute a three-page essay on "A Monastical life" by the prolific poet, playwright, and philosopher, Margaret Cavendish. While there is now a substantial body of work on nuns and convents, this research largely overlooks how early modern women engaged with these topics in a scholarly manner. Along with elucidating the gamut of relevant patristic and ecclesiastical histories that were available in the English and French vernaculars, Humble Reflections provides a prompt for investigating Cavendish's ideas on ecclesiastical order, ceremonies, and toleration. I propose that Cavendish refused to grace Du Verger with a direct response because her polemic disregarded the unofficial codes of conduct — friendship, transnational community, and inter-confessional co-existence — that were supposed to maintain peace within the Republic of Letters. In conclusion, this essay displays that Cavendish was actually a great admirer of monasticism, though not so much for its role in the spread of Christianity as for its place in the development of natural philosophy.